Brand management and its influence on commercial positioning in a customized clothing online store, Lima, 2024 - Dominguez-Bances, Yaccelinda; Fernández-Bedoya, Víctor Hugo (LACCEI, 2024)
Research aligned with SDG 8: "Decent work and economic growth", whose objective was to determine the influence of brand management on commercial positioning (and its dimensions: positioning according to competitor, positioning according to attributes and positioning according to quality) in an online shop of personalised clothing, Lima, 2024. The methodology was quantitative approach, applied type, explanatory and descriptive level, non-experimental design and cross-sectional. The population consisted of 60 customers of the shop (finite). The study sample consisted of 60 online shop customers. The technique used was the survey. It was concluded that brand management significantly influences commercial positioning in an online custom clothing shop, Lima, 2024 (sig.=0.000, r2=0.3552). Finally, conclusions and recommendations were made.